Isolated Articular Fractures of the Canine Talus: Diagnosis and Signalment in Fourteen Dogs - Carbonell Buj, Elena; Burton, Neil; Mosley, John R.; Meeson, Richard L.; Major, Alison; Whitelock, Richard G.; Parsons, Kevin; Langley-Hobbs, Sorrel J. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this retrospective multicentre case series was to describe signalment, presenting signs and imaging findings in dogs with isolated articular fractures of the talus.Study Design Medical records (2008–2019) of dogs with isolated articular talar fractures were reviewed.Results Fourteen dogs met the inclusion criteria; affected breeds were four German Pointer (three shorthair and one wirehaired), three Labrador Retrievers, two Rottweilers, two Springer Spaniels, one cross breed, one Greyhound and one Great Münsterländer. The age range was 1 to 8 years with a median of 4.7 years. Lameness was usually acute in onset and had been present for a range of 4 to 540 days prior to referral.The most common fracture configuration involved the lateral trochlear ridge only (n = 9). Two of the fourteen fractures affected both trochlear ridges. Thirteen dogs were initially assessed radiographically with classic orthogonal views, but a fracture was only visible in five cases. The remainder were confirmed with further radiographic projections (n = 4) or computed tomography (n = 5). In one case, the lameness was located to the tarsus by scintigraphy.Conclusion Isolated articular fracture of the talus is rare and may prove a diagnostic challenge due to the varied presentations and complex anatomy of the bone. Pathology of the talus may be suspected in any case of lameness localized to the tarsus and oblique/skyline radiographic views or advanced imaging should be performed if standard radiographic views are unremarkable.
Keywords: talar fracture; tarsal imaging; isolated fractures of the talus; canine talus